Injury trends in alpine skiing and a snowboarding over the decade 2008-09 to 2017-18 - Dickson, T. J.; Terwiel F. A. (Journal of Science and Medicine in Sport, 2021)
Objectives: This research explores snowsport injury trends in western Canadian resorts over the decade 2008-2018. Design: Ecological study. Methods: Injury and participation data on alpine skiing and snowboarding was provided by the Canada West Ski Areas Association for 2008-2018. Inclusion criteria were met by 29 of 52 resorts, resulting in the analysis of 107,540 injury reports via SPSS 24, using descriptive statistics and chi-squared analysis. Results: Over the decade: there was a gradual decline in the injury rate, averaging 2.24 injuries per 1000 skier days. Male snowboarders accounted for 1/3 of all injured participants, females were 42% of all. Day-ticket holders were the most injured of all customer-types, with most injuries occurring as the result of falls on marked, green/easiest terrain. For skiers, injuries to lower limbs, and especially knees, were most common. For snowboarders, upper limb injuries, especially wrists, were most common. 12.8% of the injured population required emergency transport. Advanced slopes/terrain had the highest proportion requiring emergency transport. Fewer skiers experienced head injuries than snowboarders. Snowboarders experienced a higher proportion of serious injuries. Conclusions: Snowsport injuries are relatively rare when compared to other sports. Skiers were most prone to knee injuries and snowboarders to wrist injuries. Emergency transport was proportionally needed more from advanced slopes/terrain. Further research is needed into why and how participants make decisions around risk. Future injury prevention strategies should be evaluated in light of potential risk factors such as, social determinants of injury, fall mechanisms, changing participation patterns, age, snowsport discipline, and legal cannabis use.